2019
DOI: 10.4314/rejhs.v7i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training on knowledge, attitude and practice of safety measures among battery chargers in Ilorin metropolis

Abstract: Objective: Good knowledge of safety measures against hazards of lead-acid battery work is important in the control of the work-related health problems. The study assessed the effects of training on knowledge, attitude and practice of safety measures among battery chargers in Ilorin, Nigeria. Methods: The study was a quasi-experimental (non-randomized) study with pretest and post-test design. A total of 107 battery chargers were recruited each for intervention and control group. The study group was offered trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Chimere et al (2017) found a similar result across Ibadan, Lagos, and also Aba (however, on e-waste informal workers). Chukwunonye et al (2009) revealed that the waste pickers in Nigeria are not aware of the dangers of their occupation and are concerned only with the economic benefits of the occupation; Uthman et al (2017) confirmed a similar finding in Illorin. The consequence of such negative beliefs makes it difficult for waste pickers to comply with health and safety rules.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Chimere et al (2017) found a similar result across Ibadan, Lagos, and also Aba (however, on e-waste informal workers). Chukwunonye et al (2009) revealed that the waste pickers in Nigeria are not aware of the dangers of their occupation and are concerned only with the economic benefits of the occupation; Uthman et al (2017) confirmed a similar finding in Illorin. The consequence of such negative beliefs makes it difficult for waste pickers to comply with health and safety rules.…”
Section: Introductionmentioning
confidence: 80%
“…It is of great concern to know that very little research has been conducted in the northern part of Nigeria in regard to waste picking, despite the presence of prejudice socio-economic and cultural conditions in the region which lead to the growth of the informal sector (Adama, 2014). The few available research were, however, focused primarily on the socio-economic wellbeing of waste pickers, e.g., Nzeadibe (2019), Lambu (2016); Adama (2014) and Nzeadibe et al ( & 2013, and the risk-awareness of waste scavengers, e.g., Uthman et al (2017). Eventhough, Ohajinwa et al, 2018 studied prevalence and injury patterns among electronic waste workers in Nigeria, this study has concentrated, largely, on waste pickers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the contributions of this informal sector, research on waste management in the study area has not focused on their activities and its impact on the environment. It is also important to note that least investigation has been conducted in the Northern part of Nigeria in regard to waste scavenging, the few available research were, however, focused primarily on the socio-economic wellbeing (Nzeadibe, 2009;Lambu, 2016;Adama 2014;Dankani, 2010), and the occupational health of waste scavengers, (Uthman, et al, 2017;Ohajinwa, et al, 2018;Yusuf, et al, 2021;Ali and Yusuf, 2021;Nuhu et al, 2022). However, much is not reported on the factors influencing the income of scavengers and the environmental benefits of waste scavenging.…”
Section: Issn: 2488-9229 Federal University Gusau-nigeriamentioning
confidence: 99%